The effect of caffeine supplementation on Olympic-distance triathletes and triathlon performance in the Western Cape, South Africa - Potgieter, Sunita (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.